Nilai Pendidikan Krakter dalam Cerita Legenda Masyarakat Terante: Kajian Struktural Semiotik - Agus Hi Jamal (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The aim of this study. Expanding Legend Folklore in North Maluku. of the informen who many know as well mengiventarisasi existing text in the materials area and menerjemahkanya into Indonesian conduct structural analysis of the oral literature of Ternate which includes a storyline, the main character, characters, setting the background, mandate and values contained therein gives an overview and update of the value of oral literature Ternate useful for business coaching and development and teaching. Methods This study is a qualitative research technique anlisis contents, to achieve a maksut desired with respect to the scientific effort, then peneltiti and analyze storybook legend Society Ternate, and interviewed informen to obtain data and accurate description of informen who understand and know about Public legend Ternate, in addition to the researchers collected literature tentng reference value of character education to complement the text.character education